(3x-11)×2+x=860 解方程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 19:51:22
(3x-11)×2+x=860解方程(3x-11)×2+x=860解方程(3x-11)×2+x=860解方程6x-22+x=8607x-22=8607x=882x=126
(3x-11)×2+x=860 解方程
(3x-11)×2+x=860 解方程
(3x-11)×2+x=860 解方程
6x-22+x=860
7x-22=860
7x=882
x=126
(3x-11)×2+x=860 解方程
解方程:x(2X-3)+2x(x-1)=4x(x-2)+9
解方程 x(2x-5)=4x-10 x+5x+7=3x+11
x*2x=(x+3)*2x-24 此方程怎么解?
解方程 (x²-x)²-4(2x²-2x-3)=0
解方程:(x-8)/(x-3)-(x-9)/(x-4)=(x+7)/(x+8)-(x+2)/(x+3)
解方程(x-2)X(x的平方-6x-9)=x(x-5)X(x-3)
解方程:(x²+3x)/(2x²+2x-8)+(x²+x-4)/(3x²+9x)=11/12
解方程 x-0.4x=0.3 3x+x+1.8=5 2(x+1)=解方程x-0.4x=0.3 3x+x+1.8=5 2(x+1)=6
解方程6^x+4^x=9^x,9^(-x)-2*3^(1-x)=27
解方程:(x-3)(x-5)=x(2x+1)²-11x²
解方程,x(x+3)-x(1-2x)=1+3x平方
解方程x(2x-3)+3x+3x(x-2)=5x(x-4)+11
x/(x-2)-(1-x ² )/(x ² -5x+6)=(2-x)/(x-3) 解方程,急
解方程 2乘(x-2%x)=x乘2%x解方程2乘(x-2%x)=x乘2%x
解方程3(x-2)=x(x-2)
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
解方程:(x+1)(x-1)+2(x-3)=8